Evaluation the Effects of Three Types of Pomegranate Fruit Extracts on Some Biochemical Markers and Cytogenetic Parameters in Mice Administrated With Iron Dextran to Iron Overload - Umran, Mahfoodha; Ibraheem, Shaima; Abed, Reema (Iraqi Journal of Science, 2024)
This study designed to evaluate the deleterious effects of iron overloaded on organs weights , enzyme activity of liver and bilirubin, iron concentration, total iron binding capacity in serum and on bone marrow cells proliferation in mice.The obtained results showed non significant differences in organ weights (spleen and kidney) in group 1 that treated with three parts extracts of pomegranate except the decreasing in spleen weight subgroup 1-4 , significant increasing in liver and kidney weight in all animals treated with iron dextran (group 2) in comparison with their weights of organs in negative control (group 1). While significant increasing in iron concentrations in serum of animal administrated peel and juice in comparison with their positive control, furthermore , a significant increasing in its concentration extract in serum of animal that induced iron overload. Furthermore the increasing were significant in TIBC in serum of group 2 and that level were reduced to 83.1 % ,33% and 67.1% in serum of mice post treated with seed, peel and juice respectively , and the level of TIBC were at its lowest recorded in serum of group 1, while the highest TS% were recorded in group 1 ,in contrast group 2 that revealed lower TS% especially in animal administrated iron dextran only.The study also showed significant increases in the level of AST and ALP activity and bilirubin in serum of almost all animals administrated by the three typesof pomegranate extracts,but the results also illustrated that the extracts could be reduced the highest levels of AST, ALP and bilirubin in serum of the animals with iron overload when administrated post treatment.On the other hand, the results illustrated that the juice extract induced significantly bone marrow cells proliferation in group 1 and the animals administrated iron dextran, while the administrated animals with peel and seed extracts in group 2 reduced their bone marrow cells proliferation significantly in comparison with the positive control. Non significant differences were recorded in total chromosomal aberration in bone marrow cells in group 1, while the CAs revealed significant differences in group 2 especially in animals administrated iron dextran and the type of aberrations represented was mainly of chromatid break, dicentric, a centric chromosome and ring chromosome.